2010
DOI: 10.1074/jbc.m110.107854
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Phagocytosis Requires Triacylglycerol Hydrolysis by Adipose Triglyceride Lipase

Abstract: Macrophage phagocytosis is an essential biological process in host defense and requires large amounts of energy. To date, glucose is believed to represent the prime substrate for ATP production in macrophages. To investigate the relative contribution of free fatty acids (FFAs) in this process, we determined the phagocytosis rates in normal mouse macrophages and macrophages of adipose triglyceride lipase (ATGL)-deficient mice. ATGL was shown to be the rate-limiting enzyme for the hydrolysis of lipid droplet-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
135
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 44 publications
8
135
2
1
Order By: Relevance
“…LPS-treated cells display a very robust membrane rearrangement (25,26); hence they require a high energy supply to accomplish all the remodeling that activation encompasses, including the upregulation of many genes and proteins. In fact, TAG production is increased in activated macrophages (6,(27)(28)(29), and its hydrolysis is an absolute requirement for efficient ATP supply and macrophage functioning (30). Thus, the possibility exists that in the absence of lipin-1 macrophages may not be able to meet the necessary energy levels to fulfill all their activation requirements, resulting in alteration of the whole cell reprograming.…”
Section: Discussionmentioning
confidence: 99%
“…LPS-treated cells display a very robust membrane rearrangement (25,26); hence they require a high energy supply to accomplish all the remodeling that activation encompasses, including the upregulation of many genes and proteins. In fact, TAG production is increased in activated macrophages (6,(27)(28)(29), and its hydrolysis is an absolute requirement for efficient ATP supply and macrophage functioning (30). Thus, the possibility exists that in the absence of lipin-1 macrophages may not be able to meet the necessary energy levels to fulfill all their activation requirements, resulting in alteration of the whole cell reprograming.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage phagocytosis demands a large amount of ATP and plays an essential role in host defense. Chandak et al have recently reported that a defi ciency in adipose triglyceride lipase, a rate limiting enzyme involved in the hydrolysis of lipid dropletassociated TG, in macrophages resulted in a decrease in CPT-1 expression and impaired phagocytosis ( 42 ). Others have also previously reported that macrophage LpL acts on TG-rich lipoproteins to produce FA, which is an important source of energy for phagocytosis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…FAs or their derivatives, as a ligand, can bind and activate the nuclear receptor family of transcription factors, PPARs. Desnutrin/ATGL-deficient mice with impaired lipolysis exhibited a severe defect in PPAR␣ signaling in oxidative tissues such as BAT (15), liver (54), macrophages (55), and cardiac muscle (56). In addition, adipose-tissue-specific overexpression of PPAR␦ in mice has been shown to enhance the expression of genes for FA oxidation (57).…”
Section: Discussionmentioning
confidence: 99%